2-Dimethylamino-1-(2-ethoxy-2-oxoethyl)-3-methyl-4,5-dihydroimidazolium tetraphenylborate - Ioannis Tiritiris; Willi Kantlehner (IUCrData, 2016)
In the crystal structure of the title salt, C10H20N3O2+·C24H20B−, the C—N bond lengths in the cation are 1.327 (3), 1.339 (3) and 1.342 (3) Å, indicating partial double-bond character. The central C atom is bonded to the three N atoms, indicating only a slight deviation from a trigonal–planar geometry. The positive charge is delocalized in the CN3 plane. The ethoxy group is disordered over two orientations, with an occupancy ratio of 0.60 (1):0.40 (1). C—H...π interactions are present between the guanidinium H atoms and the phenyl C atoms of the tetraphenylborate ions. The phenyl rings form aromatic pockets, in which the cations are embedded. This leads to the formation of a two-dimensional supramolecular pattern along the ac plane.